1992
DOI: 10.1016/s0006-3495(92)81801-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of non-beta 6.3-helical gramicidin channels between sequence-substituted gramicidin analogues

Abstract: Using the linear gramicidins as an example, we have previously shown how the statistical properties of heterodimeric (hybrid) channels (formed between the parent [Val1]gramicidin A (gA) and a sequence-altered analogue) can be used to assess whether the analogue forms channels that are structurally equivalent to the parent channels (Durkin, J. T., R. E. Koeppe II, and O. S. Andersen. 1990. J. Mol. Biol. 211:221-234). Generally, the gramicidins are tolerant of amino acid sequence alterations. We report here an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
138
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(148 citation statements)
references
References 35 publications
10
138
0
Order By: Relevance
“…The four Trps at the C-terminal cluster at the membrane-water interface (Fig. 1C) and are important for the SS conformational preference of gA in lipid bilayers (18,19). The DS structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The four Trps at the C-terminal cluster at the membrane-water interface (Fig. 1C) and are important for the SS conformational preference of gA in lipid bilayers (18,19). The DS structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments on gA 3 suggested that the indole dipole moment (13)(14)(15)(16)(17) has a direct influence on membrane protein function (ion permeation) and that indole NH hydrogen bonding is important for the conformational preference of gA (18,19). More generally, indole N-H hydrogen bonding appears to be important for protein folding and dynamics (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1c). The energetic cost of burying the amphipathic Trp residues will destabilize the DS channels relative to their SS counterparts 14 ; one cannot neglect the importance of the (membrane) environment for the gramicidin's conformational preference.…”
mentioning
confidence: 99%